Treatment with Mycophenolat Mofetil of Steroid-Dependent Asthma—One Case of Severe Asthma. (7th October 2009) - Backer, V.; Hjardem, E.; Karlsmark, T.
Abstract : Background . Some patients with severe nonallergic asthma can be difficult to treat with conventional therapy. Mycophenolat Mofetil (MMF) is an immunosuppressive drug with multiple mechanisms. There is theoretical support of specific effect of MMF on severe asthma, in "difficult to treat" patients. The aim of the present case was to explore whether MMF had an effect in one case of severe refractory asthma. The patient . This case deals with one patient with very severe nonallergic treatment refractory asthma who experienced treatment failure on ordinary antiasthmatic treatment and severe adverse events to conventional immunosupressive treatment. She was then treated with MMF. Results . The patient experienced a gain in FEV1 and a reduction in the need for oral glucocorticosteroids as well as seldom need of when needed bronchodilator both during daytime and night. It therefore seems very interesting to examine the use of MMF for severe refractory asthma with further clinical studies and basic cellular trials.